Seismic Stability Analysis of Saturated and Unsaturated Soil Slopes Using Permanent Displacement - Shuai Huang; Yanju Peng (Advances in Civil Engineering)
The permanent displacement has been widely used for slope seismic stability in practical engineering; however, the effect of the dynamic pore water pressure on the saturated and unsaturated soil slopes could not be neglected. In this paper, we propose a calculation method of dynamic pore water pressure by the hollow cylinder apparatus (GCTS) which is the most advanced and complicated device in lab testing on soil dynamics. Then, based on the proposed calculation method of dynamic pore water pressure combined with the limit equilibrium and finite element methods, we introduce a simple calculation method of permanent displacement, which avoids solving complex nonlinear equations and greatly simplifies the computational effort. Shaking table test results demonstrate the effectiveness and efficiency of the simple calculation method of permanent displacement, which could rapidly assess the soil slope seismic stability considering the effect of dynamic pore water pressure.